PTU-019 Antithrombotic Vs. Ulcer Effects In Non-variceal Bleeding In Users Of Antithrombotic Drugs. (9th June 2014) - Taha, AS; McCloskey, C; Craigen, T; Angerson, WJ
Abstract : Introduction: The use of antithrombotic drugs (ATDs) remains a considerable challenge in the aetiology and management of non-variceal upper gastrointestinal bleeding (NVUGIB). In the upper gastrointestinal tract, ATD use may result in bleeding by mucosal damage (ulcer effect) or through its basic antithrombotic effect. The clinical significance of these effects is unclear. In this controlled analysis, we AIMED to clarify the significance of the antithrombotic effect as compared with the ulcer effect in patients with NVUGIB using ATDs. Methods: We previously found that ATD users tended to be older and to have higher comorbidity and different endoscopy findings. To overcome these confounding factors, we compared 202 patients with NVUGIB using ATDs (ATD Group) with 202 patients with NVUGIB but not using ATDs (Controls), having matched both groups in a pairwise manner for age, Charlson comorbidity score and a composite endoscopic score covering the oesophagus, stomach, and duodenum. Antithrombotic drugs included low-dose aspirin, clopidogrel, dipyridamole, warfarin, and heparin. Patients using NSAIDs were excluded. Characteristics of the groups were compared using the Wilcoxon signed rank test and McNemar's test. Continuous variables are reported as median (IQR). Results: The characteristics of the two matched study groups are shown in Table 1 . Conclusion: After matching for age, comorbidity, and composite endoscopy score, patients with NVUGIB and using ATDs had significantly lower haemoglobin level, higher Blatchford risk score, and were 1.5 times more likely to be transfused. These effects are most likely to be due to the antithrombotic activity of ATDs rather than ulcers alone, and they need to be considered in the management of NVUGIB. Disclosure of Interest: A. Taha Consultant for: Almiral Pharma UK, Vifor Pharma UK, Horizon Pharma USA, C. McCloskey: None Declared, T. Craigen: None Declared, W. Angerson: None Declared.